Estimation of the impact of social determinants on childhood obesity in the Apulia region (southern Italy) in 2019: Impact of social determinants on childhood obesity - Balducci, Maria Teresa; De Giglio, Osvalda; Quaranta, Alessia; Pedote, Pasquale Domenico; Pasquale, Pietro; Mongelli, Onofrio; Montagna, Maria Teresa (Progress in Nutrition, 2022)
Background and aim: The nutritional status of a population is an important determinant of its health condition and the obesity represents one of the emergencies in Public Health. The health outcomes related to chronic diseases are mainly derived from specific risk factors and the social determinants can often be the causes of the causes of these risk factors. The aim of the study was to estimate the extent to which the effects of some social determinants (economic difficulty and the parental level of education) can influence obesity in primary school children residing in the Apulia region and to evaluate the potential health gain that children could have by improving the those social determinants.Methods: The contribution of social determinants to the onset of the obesity risk factor in children was calculated with arithmetic proportion software called CoEsDi Children (Contribution to the Exposure of Inequalities). This software used as a data source the regional survey, Okkio alla Salute—Puglia 2019, which studied the prevalence of obesity in children and the social determinants of their parents. The data analysis was mainly aimed at estimating the prevalence of the detected variables, setting the confidence interval at 95%.Results: Forty-three percent of obese Apulian children who have parents with low levels of education and severe economic difficulties would be able to reduce their weight status if social inequalities were changed, and 7% would not be able to develop obesity if they were raised in a family without social inequalities.Conclusions: Obesity in children is closely related to the socio-economic status of the parents: the higher the level of income inequality is, the more overweight the children are.The interconnected nature of the determinants of obesity implies a need for an integrated response that includes action at the community level, political will, and investment.